Adubação fosfatada e qualidade de luz no crescimento e desenvolvimento do amendoinzeiro no Recôncavo Baiano - Souza, Ubiratan Oliveira (2009)
In Recôncavo of Bahia, the groundnut is grown during the rainy season, reaching a productivity below the national average. Phosphorus is the nutrient that most limits their production. However, physiological processes can be optimized, when subjected to different qualities of light. In order to evaluate the interaction between the phosphorus and the quality of light in the development of peanut grown in an Yellow Latosol, an experiment was installed in CCAAB - UFRB in Cruz das Almas - BA. The experimental design was in bands in 4 x 4 factorial, with three replicates, and the treatments with P corresponded to 0, 50, 100 and 200 kg ha-1 P2O5 and four qualities of light: red mesh, blue mesh, silver mesh and full sun. Each experimental unit was composed of five lines of sowing, containing 45 useful plants, spaced with 50 cm between and 20 cm between plants, using the cultivar pods Lisa. After 30 and 92 DAS, carried out the crops. The plants were fractionated into roots, stems and leaves to get the drying and dry. Determined by whether the biometric measures linear and nonlinear, productivity, content of N, P and K in plants, as well as the concentrations of protein and oil in grains. It was found that the interaction between phosphorus levels and qualities of light, was significant for most of the observed variables, generating increases in rates of physiological development, productivity, culture, content of nutrients in the plant and the yield of protein and peanut oil in grain, and striking the upper end of the red mesh, especially when associated with the highest levels of phosphorus.